Efficacy of feed ingredient with probiotics properties, on the growth performance and health of Giant White Bouscat Red Eye Rabbits - GNIKPO, Aristide; CHRYSOSTOME, CHRISTOPHE ACHILLE A. MAHUSSI; HOUNDONOUGBO, M. FRÉDÉRIC; DOUGNON, T. VICTORIEN; LIBANIO, Dahouda (My University, 2017)
This study aims to evaluate the efficiency of a feed ingredient with probiotic properties (FIPP) on growth performances of Giant White Bouscat red eye rabbits. The experiment was carried out during 56 days on 150 weaned rabbits in Cuniglo farm in Southern of Benin. Rabbit had 35 days-old and weighted on average 669.94 ± 69.55 g. The experimental design was a randomized complete block with five dietary treatments (TF0, T0, T1.5, T3 and T4.5) and six replicates per treatment. TF0 rabbits were fed with the control diet and received antibiotics, T0 rabbits were fed only with the control diet; T1.5, T3 and T4.5 rabbits were fed with the control diet supplemented with 1.5%, 3% and 4.5% of FIPP respectively. The results showed that the rabbits fed TF0, T1.5 and T3 had the best weight performances compare to those fed T0 and T4.5% dietary treatments. Hematological, mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC) (p=0.058) and lymphocyte (LYM) are improved with the supplementation of FIPP. The lowest feed cost was in T3 (1815 FCFA/kg weight gain) followed by TF0 (1812 FCFA/kg weight gain); T1.5 (1860 FCFA/kg weight gain); T0 (2144 FCFA/kg weight gain) and T4.5 (2859 FCFA / kg weight gain). The economic feed efficiency had the same trends as feed costs. We can conclude that FIPP at concentrations of 1.5% and 3% had an effect on growth performances and on blood characteristics of rabbits
Keywords: Rabbit; feed; growth; probiotic; hematology; efficiency